Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.

Nickel ferrite nanoparticles-hydrogen peroxide: a green catalyst-oxidant combination in chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides - Kulkarni, Aparna M.; Desai, Uday V.; Pandit, Kapil S.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Nickel ferrite nanoparticles-hydrogen peroxide has been demonstrated for the first time as a green and efficient catalyst-oxidant combination in the chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides. This magnetically separable catalyst was found to be reusable for five consecutive runs without appreciable change in the activity, as well as composition of the catalyst. The mechanism for the oxidation of thiols and sulfides has also been proposed.

Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.

Tris-hydroxymethylaminomethane (THAM): a novel organocatalyst for a environmentally benign synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles - Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2015)
simple, efficient and environmentally benign protocol has been developed for the one-pot, multicomponent synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles using a commercially available, inexpensive, non-toxic, and biodegradable tris-hydroxymethylaminomethane (THAM) as a novel organocatalyst. Ambient reaction conditions, wide scope, avoidance of conventional isolation as well as purification techniques and the reusability of the catalyst for five consecutive runs have improved the practical utility of this multicomponent reaction protocol manifold.

Diethylamine-catalyzed environmentally benign synthesis of 1-oxo-hexahydroxanthenes and bis-coumarins at ambient temperature - Kupwade, Ravindra V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (Research on Chemical Intermediates, 2016)
An extremely simple, economical and environmentally benign protocol has been described for one-pot synthesis of 1-oxo-hexahydroxanthenes by pseudo three-component condensation between salicylaldehydes and dimedone, cyclohexane-1,3dione or 5-methyl cyclohexane-1,3-dione using diethylamine as the catalyst. Based upon the mechanism of the reaction, the protocol has been extended towards the synthesis of tetraketones and bis-coumarins.

Problem solving and environmentally benign approach toward diversity oriented synthesis of novel 2-amino-3-phenyl (or Alkyl) sulfonyl-4H-chromenes at ambient temperature - Pandit, Kapil S.; Kupwade, Ravindra V.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (ACS Sustainable Chemistry & Engineering, 2016)
A problem solving, environmentally benign, and diversity oriented protocol has been described for multi component synthesis of medicinally privileged 2-amino-3-phenyl (or methyl) sulfonyl-4H-chromenes by one-pot, three component condensation among aldehydes, phenyl (or methyl) sulphonyl acetonitrile, and alpha-naphthol, 3-dimethylamino phenol, 4-hydroxy-N-methyl-quinoline-2-one as well as 4-hydroxycarbazole, using diethylamine as an efficient organo catalyst. The catalyst employed is commercially available, inexpensive, and nontoxic. Ambient reaction conditions, very high yields, wide scope, and avoidance of conventional isolation as well as chromatographic purification have improved the practical utility of this protocol manifold.
Keywords: 2-Amino-3-methylsulfonyl-4H-chromenes; 2-Amino-3-phenylsulfonyl-4H-chromenes; diethylamine; green chemistry; Multicomponent synthesis; organocatalyst

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Sulfamic acid-catalyzed, environmentally benign synthesis of bis-tetronic acids at ambient temperature - Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (Research on Chemical Intermediates, 2017)
An enviro-economic protocol has been described for the synthesis of bis-tetronic acids by pseudo-three-component condensation between aldehydes/isatins and tetronic acid using sulfamic acid as a solid acid catalyst. Easy commercial availability of the catalyst at extremely low cost, excellent yields and avoidance of conventional purification procedures are the main merits of this energy efficient protocol.